The Use of the Fibrinogen Turnover and the Isotope Scanning of the Legs for the Diagnosis of Venous Thrombosis in Non Surgical Patients - den Ottolander, G. J. H; van der Maas, A. P. C; Schopman, W (Thrombosis and Haemostasis, 1974)
In 2 groups of non surgical patients with venous thrombosis (V. T.) the fibrinogen turnover rate was determined in addition to scanning of the legs.In the first group of 13 patients with clinical signs of V. T. the Tx/2 of 131I-fibrinogen was shorter than in a normal group. In the second group of 10 patients with V. T., diagnosed only by local scanning of the legs using 125I-fibrinogen, the T72 was also shortened.Because of the longer half life time of the 125I-label, observations can be carried out during a period of 20 days, so that 125I-fibrinogen is preferable to 131I-fibrinogen. Of 33 elderly patients treated for congestive heart failure a positive leg scan was observed in 15. Treatment with intravenously injected heparin immediately interferes with further accumulation of radioactivity and corrects the shortened TVa to normal values, in contrast to treatment with oral anticoagulants.